Intraurethral alprostadil in the management of erectile dysfunction: a reappraisal of the clinical evidence. (March 2014) - Dinsmore, Wallace; Lopes, Tomé Manuel; Potempa, Axel-Jürg; Piha, Juhana; Costa, Pierre
During the next decade, it is estimated that erectile dysfunction (ED) will affect >320 million men worldwide. Intraurethral alprostadil provides an effective, well-established treatment option for men with ED. The current article provides a descriptive reappraisal of the clinical evidence gained with intraurethral alprostadil (administered using the Medicated Urethral System for Erection [MUSE ® ]; MEDA, Madrid, Spain) in the management of ED. In well-designed clinical trials, intraurethral alprostadil demonstrated clinical success in up to approximately 70% of patients, was associated with a relatively low incidence of mainly mild adverse events (most commonly penile pain) and no incidence of priapism or fibrosis, was well accepted by patients, and improved key quality-of-life domains in patients and their partners. Similar efficacy rates have also been demonstrated with intraurethral alprostadil in patients with diabetes, vascular disease, neuropathy, alcohol/tobacco abuse, after surgery (e.g., radical prostatectomy) or trauma (e.g., spinal cord injury), and in patients failing oral therapy or penile implants/prostheses (a contraindication for intracavernous injection therapy). A few clinical trials have directly compared intraurethral and intracavernous injection of alprostadil in the management of ED. In general, patient acceptance and/or safety were higher with intraurethral administration compared with intracavernosal, although the latter demonstrated better efficacy. In combination with oral phosphodiesterase type 5 inhibitors, intraurethral alprostadil has been shown to be a viable salvage option in patients with ED who have a suboptimal response to monotherapy and the desire for minimally invasive therapy. In summary, intraurethral alprostadil provides a noninvasive, safe and effective treatment option in men with ED. Given the current unmet medical gap between the use of oral medications and second-line treatment using invasive intracavernosal injections, and based on American Urological Association recommendations for appropriate treatment options to be applied in a stepwise fashion with increasing invasiveness, intraurethral alprostadil represents a first-choice option in patients in whom phosphodiesterase type 5 inhibitors have failed or are contraindicated.